0548 Vibro-tactile Induced Postural Change Improves Sleep Quality. (12th April 2019) - French, John; Bush, Dylan; Murph, Imani; Mortimer, Bruce
Abstract: Introduction: Loud, persistent snoring reduces the quality of sleep and has been linked to severe daytime fatigue, obesity and sleep apnea. Most snoring is positional and is most prominent while sleeping on the back. A vibro-tactile sleep belt was designed to promote a postural change and induce sleeping on the side as a means to reduce snoring. Methods: The belt consisted of 2 small vibrating disks that were embedded in an elastic strap such that they would make contact with the sleepers back. Velcro strips were used to affix the elastic belt. Body pressure on the disks activated a high frequency vibration after a five second delay which remained activated until postural change occurred. The effect on sleep quality was measured over 3 nights without the belt and 3 nights with the belt in 5 persons who were determined to be heavy snorers and 5 persons who were not heavy snorers. Results: The average time the disks were activated decreased from 63 minutes in an average sleep of 7.3 hours on the first night to less than 30 minutes for the remaining 2 nights. Actigraph data indicated that the percent of time asleep was algorithmically scored at 55% without the belt for heavy snorers. This increased significantly to over 88% for the same participants over the nights the belt was worn. Sonographic analysis indicated a dramatic decrease in snoring from non-belt nights to belt nights in the heavy snorers. Daytime fatigue scores were decreased in all from an incidence of 15 ratings of great fatigue without the belt to 8 ratings with the belt worn at night. Conclusion: Conventional devices worn to prevent snoring such as a mouthpiece must be worn every night. The sleep belt trains the individual to sleep on the side. It was effective at promoting sleep off the back, improving time asleep, reducing snoring and daytime fatigue. This device may have usefulness in improving the quality of sleep otherwise impacted by snoring. Support (If Any): The study was supported by a student research grant from Embry-Riddle University.